2008
DOI: 10.1177/154405910808700109
|View full text |Cite
|
Sign up to set email alerts
|

Premature Stop Codon in MMP20 Causing Amelogenesis Imperfecta

Abstract: Proteolytic enzymes are necessary for the hardening of dental enamel during development, and mutations in the kallikrein 4 (KLK4) and enamelysin (MMP20) genes cause autosomal recessive amelogenesis imperfecta (ARAI). So far, only one KLK4 and two MMP20 mutations have been reported. We have identified an ARAI-causing point mutation (c.l02G>A, g.l02G>A, and p.W34X) in exon 1 of MMP20 in a proband with autosomal recessive hypoplastic-hypomaturation amelogenesis imperfecta. The G to A transition changes the trypto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 32 publications
3
61
0
Order By: Relevance
“…One of these mutations encodes a stop signal in the propeptide-coding region of exon 1 [30]. Enamel in the afflicted individual is thin, hypomineralized and chips Tooth gene evolution in baleen whales R. W. Meredith et al 995 away from the underlying dentin [30]. Disease-causing SINE insertions in exons are sometimes associated with multiple transcripts, including mRNAs in which the SINE-afflicted exon has been spliced out [46].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One of these mutations encodes a stop signal in the propeptide-coding region of exon 1 [30]. Enamel in the afflicted individual is thin, hypomineralized and chips Tooth gene evolution in baleen whales R. W. Meredith et al 995 away from the underlying dentin [30]. Disease-causing SINE insertions in exons are sometimes associated with multiple transcripts, including mRNAs in which the SINE-afflicted exon has been spliced out [46].…”
Section: Resultsmentioning
confidence: 99%
“…Three mutations in the human MMP20 gene that cause amelogenesis imperfecta have been characterized, and in every case the inheritance pattern is autosomal recessive. One of these mutations encodes a stop signal in the propeptide-coding region of exon 1 [30]. Enamel in the afflicted individual is thin, hypomineralized and chips Tooth gene evolution in baleen whales R. W. Meredith et al 995 away from the underlying dentin [30].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eventually it was demonstrated that two proteases are involved: matrix metalloproteinase 20 (Bartlett et al, 1996) and kallikrein 4 . These enzymes undoubtedly play critical roles in dental enamel formation, as mutations in MMP20 and KLK4 cause autosomal recessive amelogenesis imperfecta (Hart et al, 2004;Kim et al, 2005;Ozdemir et al, 2005;Papagerakis et al, 2008). The functions of MMP-20 and KLK4 are best explained in the context of how enamel forms.…”
Section: Dental Enamelmentioning
confidence: 99%